Analysis of Financing in Education Sector and Human Development Index in Regencies/City - Rio Hermawan; Muhammad Amir Arham; Sri Indriyani Dai (Universitas Gorontalo, 2022)
The research aims to analyze the effect of financing in education sector by utilizing data from statistics of Gorontalo Province from 2015 to 2019 in five regencies and one city administration in Gorontalo Province. Therefore, the proper analysis tool to use is panel data regression and fixed effect model (FEM). The result of analysis shows that there is a positive and significant effect of financing in education sector on the human Development Index as an increase in the financing will lead to an increase in the Human Development Index too. In addition, the control variable used is Gross Participation Rate (APK) for senior High School owns a negative and insignificant effect on the human development Index. In the meantime, the Net participation Rate (APM) for senior High School owns a positive and significant effect on the increase of Human Development Index. Additionally, the use of education budget requires to be increased whether in measurable planning process distribution or productive spending. Therefore, it is indispensable to perform sustainable monitoring and evaluation from all stakeholders.